Hubungan antara Berat Badan Berlebih dengan Terjadinya Sindrom Syok Dengue pada Anak di RSD dr. Soebandi, Jember - Hana Nabilah; M. Ali Shadikin; Rony Prasetyo (Pustaka Kesehatan, 2019)
Dengue Shock Syndrome (DSS) is shock syndrome that happened in dengue hemorrhagic fever patients. There are risk factors that cause DSS. One of them is overweight in children. This study aimed to determine the relationship between overweight and the occurence of DSS. This retrospective case control study conducted at the dr. Soebandi Hospital Jember. Sampels were divided into DSS group (case group) and non-DSS group (control group). To analyze the data, Chi-Square test was performed using SPSS version 21. Aa many as 191 patients were included in this study which consisted of 132 patients as the control group and 59 patients as the case group. Chi-square analysis showed the p-value was 0,649. In conclusion, overweight was not significantly associated as a risk factor of DSS in children at the dr. Soebandi hospital.